2016
DOI: 10.5146/tjpath.2015.01340
|View full text |Cite
|
Sign up to set email alerts
|

Primary paediatric renal primitive neuroectodermal tumor: a case report and review of the literature

Abstract: Ewing sarcoma/primitive neuroectodermal tumor (PNET) is a high-grade malignant neoplasm commonly affecting bones of the thoracic region. Primary Ewing sarcoma/PNET of the kidney is exceptional; it commonly affects young adults and is rarely reported in children. Here we describe a case of renal PNET in a 10-year-old girl who presented at our institute with haematuria and abdominal lump. Computer tomography scan revealed a huge mass in the right kidney. Computer tomography-guided aspiration from the mass showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Risi ( 3 ) reported that 54% of patients presented with pain, 28% with a bulky renal mass, and 29% with hematuria. Compared to other renal tumors, rPNET malignancy is more common, prone to recurrence after surgery, and more likely to metastasize, with the most common sites of metastasis being the lungs, followed by the liver and bones ( 4 ). There are also early renal vein or inferior vena cava cancer thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…Risi ( 3 ) reported that 54% of patients presented with pain, 28% with a bulky renal mass, and 29% with hematuria. Compared to other renal tumors, rPNET malignancy is more common, prone to recurrence after surgery, and more likely to metastasize, with the most common sites of metastasis being the lungs, followed by the liver and bones ( 4 ). There are also early renal vein or inferior vena cava cancer thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…Primary renal ESFT presents major diagnostic and management hurdles for providers, as these patients most often present with advanced staging with extrarenal extension and metastases. [4][5][6][7][8][9] The optimal management of ESFT continues to be debated. However, current standard of practice invokes a combination of chemotherapy, surgical resection, and/or radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the rarity in presentation, there are many case reports and several case series that echo the aggressive clinical features, high propensity for metastasis, and overall poor outcome. 1,[4][5][6][7][8][9][10] In this paper, we present seven pediatric and young adult patients with primary renal ESFT and one patient with primary adrenal disease.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 It is uncommon in children below the age of 15 years, with only a few cases reported thus far. 4 Due to its rarity, renal PNET is usually not suspected and pose a challenge to distinguish this from other more prevalent kidney tumors. 2,5 In this report, we describe the case of a 14year-old girl who presented with renal mass and was ultimately diagnosed with renal PNET.…”
Section: Introductionmentioning
confidence: 99%